PERTIMBANGAN HAKIM DALAM PENJATUHAN PIDANA TERHADAP ANAK SEBAGAI PELAKUTINDAK PIDANA PERBUATAN CABUL - Gulo, Herman Leonard (LPPM Universitas Nias Raya, 2024)
Before making a decision on a case, the judge uses the judge's consideration, which is an argument or reason used as a legal consideration. The crook demonstration of vulgarity is a wrongdoing carried out by somebody who disregards respectability and goodness or it can likewise be a grievous demonstration which falls inside the domain of desire. for example, contacting privates, kissing, contacting bosoms, etc. A kid is somebody who isn't yet 18 (eighteen) years of age, remembering youngsters for the belly. A youngster is somebody who is brought into the world from a marriage between a lady and a man, despite the fact that they are not hitched, they are as yet supposed to be kids. Additionally, the judge's consideration has benefits for the parties involved, necessitating that it be addressed properly in the present case. According to Decision Number 3/Pid, the author's sentence was more severe than the public prosecutor's indictment. Sus-Anak/2022/PN. Gst, the appointed authority condemned the respondent to jail for quite a long time and occupation preparing for quite a long time. This paper asks whether the judge's reasoning for imposing a sentence that is greater than the maximum threat for the crime of threatening violence in decision number 3/Pid is sound. Sus-Anak/2022/PN.Gst. The author carried out normative research employing the case method, analytical approach, and statutory regulatory approach. Information assortment was completed utilizing auxiliary information, which was acquired through library materials comprising of lawful materials essential and optional legitimate materials. The information investigation utilized is graphic subjective examination and decisions are made utilizing a rational technique. For the situation brought by the creator up in agreement with concentrate on choice number 3/Pid. Sus-Anak/2022/PN. Gst, the creator found a few things that turned into the reason for this issue, specifically the adjudicator's heedlessness in choosing the case, answering and looking at the proof in the preliminary and furthermore the exclusion of the beating of the culprit by the examiner during the examination.